If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 32 = 11x + -94 Reorder the terms: 32 + 4x = 11x + -94 Reorder the terms: 32 + 4x = -94 + 11x Solving 32 + 4x = -94 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 32 + 4x + -11x = -94 + 11x + -11x Combine like terms: 4x + -11x = -7x 32 + -7x = -94 + 11x + -11x Combine like terms: 11x + -11x = 0 32 + -7x = -94 + 0 32 + -7x = -94 Add '-32' to each side of the equation. 32 + -32 + -7x = -94 + -32 Combine like terms: 32 + -32 = 0 0 + -7x = -94 + -32 -7x = -94 + -32 Combine like terms: -94 + -32 = -126 -7x = -126 Divide each side by '-7'. x = 18 Simplifying x = 18
| y^4-2y^2-8=0 | | 3x-6x+5x-9x= | | (x*5)+(.1x*15)=3260 | | 6x-3-2x=17 | | (48-3)/5=x | | s=.5gt | | 9(q+2)= | | 5e+8=56 | | 4x=11-3 | | 7x-4=-2x+1+9 | | 5(7y)= | | 3x+34=6x+10x | | (3x-3)+(3x-3)+(x-3)+(x-3)=(2x-1)+(2x-1)+(2x) | | 2x-6x+7x-5x= | | 28.75=2.50+3.75x | | -7x-5x=8-8x | | 3x+40=6x+7 | | 6-7(x+1)=-3(2-x) | | .32+.20x=2.32 | | 4x+29=7x+8 | | 7x-13y=32 | | 7x+2=5x+4 | | 3x-3*x-3=2x-1+2x+2x-1 | | 4x=10-3 | | 4=24.2x | | 5x-45=4x+36 | | 4x+33=6x+5 | | 7(3-4n)=12n-19 | | 6y-4(y-1)+3= | | 2x+3-7x=28 | | 4x=11+1 | | 2.2k-4.3=12.6k+14.5 |